Adoption of Auto-replenishment as Digital Transformation Solution For Supply Chain Operation In Gas Station Using TAM-TOE Framework - Ferdian Adhika Kurniawan; Jonathan Nahum Marpaung (Journal La Multiapp, 2026)
Indonesia’s downstream oil and gas sector faces persistent supply chain challenges due to manual processes and high demand variability. This study aims to investigate the determinants influencing the behavioral intention of Indonesian Gas Station (SPBU) operators and supervisors to adopt the Auto-Replenishment system. Data were collected from 419 valid respondents of gas station operators and supervisors who had completed the Digitalisasi SPBU e-learning. The model comprises nine latent constructs from Technology Organization Environment and Technology Acceptance Model Framework. Data were analyzed using Partial Least Squares–Structural Equation Modelling (PLS-SEM), and reveals that Top Management Support and Organizational Readiness are the strongest drivers, significantly enhancing both Perceived Usefulness and Perceived Ease of Use. Environmental factors, specifically Regulatory Support and Vendor Support, significantly impact Perceived Ease of Use. Technological Readiness influenced Perceived Usefulness but failed to significantly affect Perceived Ease of Use. In line with TAM, both Perceived Usefulness and Perceived Ease of Use have significant positive effects on Behavioral Intention, and mediation analysis confirms that these TAM constructs transmit a substantial portion of TOE effects to adoption intention.